Standardization of Agent-based Modeling in Economic System - Li, Xihao (Discontinuity, Nonlinearity, and Complexity, 2026)
This work combines generic complexity of economic system and economic agents with methodologies of multi-agent system analysis and development. This combination results in an integrative framework that serves as communication protocol for delivering and transmitting agent-based model for economic system. The integrative framework provides guidance for analyzing economic system in micro-level, which embeds with properties of complexity in structure, heterogeneity in agents’ beliefs, and interactions among agents’ behaviors. It provides routines on developing standardized agent-based model for economic system that can be used and reused among interdisciplinary research.